Chemical analysis of surface and bulk of asphalt binders aged with accelerated weathering tester and standard aging methods. (15th August 2017) - Menapace, Ilaria; Yiming, Wubulikasimu; Masad, Eyad
Highlights: Asphalt binders were aged with an accelerated weathering tester using UV radiation. FTIR and XPS detected more chemical changes with this method than standard methods. As aging proceeded, oxygen, nitrogen and sulfur concentrations on the surface increased. Binder oxidation is much higher on the surface than in deeper layers. In homogenous samples surface composition differed from bulk due to microstructures. Abstract: This paper presents analysis of chemical changes in asphalt binder samples that were aged using an accelerated weathering tester, which involves UV radiation and direct aging of the binder surface. It also provides a comparison with chemical changes in the same binders but aged with standard methods. Fourier Transform Infrared (FTIR) and X-ray photoelectron spectroscopy (XPS) results show that the accelerated weathering tester caused more extensive chemical changes, such as higher oxidation and inclusion of nitrogen from the air, compared to standard aging methods. The amount of oxygen, nitrogen and sulfur on the surface was observed to increase as aging time increased. In addition, the XPS etching analysis highlighted that the depth profile of binders changed from the surface to deeper layers and showed that the directly aged samples using the weathering tester were heavily oxidized on the surface and less on the underlying layers. Unaged binders and binders aged with standard methods displayed a fairly uniform depth profile. However, slight differences in the chemical composition were detected on the surface of these samples, which were associated with the surface microstructure developed during sample preparation. The results of the chemical characterization are compared in this paper with previous findings in terms of microstructural configuration that were obtained using Atomic Force Microscopy (AFM).